1995
DOI: 10.1002/ar.1092420204
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong moderate running training increases the incidence and severity of osteoarthritis in the knee joint of C57BL mice

Abstract: According to our results, the moderate, long-lasting running exercise accelerates the development of osteoarthritis in the knee joints of C57BL mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 42 publications
6
44
0
Order By: Relevance
“…Rats who ran on a treadmill between the ages of 6 and 24 months showed more severe OA in the knee joints than did the control animals [62]. Lifelong moderate running (1 km/day) on a treadmill between 2 and 18 months of age increased the incidence and severity of OA in the knee joints of C57BL mice [63]. However, lifelong moderate running of beagle dogs showed no evidence of knee articular cartilage injury after 4 km/ day exercise on the treadmill, 5 days/weeks, for a total of 550 weeks [64].…”
Section: Increased Joint Loading and Weight-bearingmentioning
confidence: 91%
“…Rats who ran on a treadmill between the ages of 6 and 24 months showed more severe OA in the knee joints than did the control animals [62]. Lifelong moderate running (1 km/day) on a treadmill between 2 and 18 months of age increased the incidence and severity of OA in the knee joints of C57BL mice [63]. However, lifelong moderate running of beagle dogs showed no evidence of knee articular cartilage injury after 4 km/ day exercise on the treadmill, 5 days/weeks, for a total of 550 weeks [64].…”
Section: Increased Joint Loading and Weight-bearingmentioning
confidence: 91%
“…Similar downhill running regimens have been used in other studies of exercise effects in rats [8]. The running exercise was used primarily to standardize the minimal amount of exercise all rats were doing but also because we assumed joint loading might need to be greater than that of cage activity for the development of osteoarthritis [12,16,28]. Rats were housed in pairs and were monitored daily.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, in OA, the PGs of the superficial zone experience loss and the collagen fibril network in the surface-most cartilage becomes progressively disorganized [14][15][16][17]. Earlier findings have indicated that exercise may protect from OA, make the joint more prone to OA, or have no effect on the incidence of OA [8,[18][19][20][21][22]. Part of this controversy may be explained by variations in the amount of exercise and its duration, as well as the site investigated in the joint [16].…”
Section: Introductionmentioning
confidence: 99%
“…Hypothetically, the modification of cartilage composition due to exercise could protect the joint from OA during later periods of life [18,23]. Investigations of the simultaneous effects of aging and exercise on cartilage with different animal models have reported various types of outcomes [8,19,24]. Lifelong moderate and non-voluntary running exercise of C57BL mice between the ages of 2 and 18 months was shown to increase the incidence and severity of OA [19].…”
Section: Introductionmentioning
confidence: 99%